T1-weighted MR imaging of bone marrow pattern in children with adolescent idiopathic scoliosis: A preliminary study. (April 2018) - Shiran, S. I.; Shabtai, L.; Ben-Sira, L.; Ovadia, D.; Wientroub, S.
Purpose: Distinct normal physiological patterns of fat conversion in vertebrae were described both for children and adults. Our aim was to evaluate the T1-weighted bone marrow pattern of the vertebral bodies in various sites along the scoliotic spine of children with adolescent idiopathic scoliosis (AIS). Methods: We retrospectively evaluated spine MRI studies of children with AIS. Scoliosis radiographs were assessed for type of curvature according to the Lenke classification. A paediatric neuroradiologist assessed the T1-weighted signal of vertebral bodies in comparison with the adjacent disc and distinct patterns of fatty conversion within the apical and stable vertebral bodies. Statistical assessment was performed. Results: MRI study of the spines of 75 children with AIS were assessed, 59 (79%) of whom were female, with an age range of nine to 19 years. The relative overall T1-weighted signal intensity of the vertebral body bone marrow relative to the intervertebral disc was hyperintense in 76% and isointense in 24%. Fatty conversion grade of the stable vertebra was higher than the apex vertebra (p = 0.0001). A significant tendency to have more advanced fat conversion patterns in the apex vertebra up to age 13.5 years old compared with adolescents above that (p = 0.015) was seen. Conclusion: This preliminary study suggests a different pattern of bone marrow conversion in AIS from the normal physiologic pattern described in the literature. Whether these changes are secondary to the biomechanics of the curved spine or may suggest that bone marrow maturation rate and content have a role in the pathogenesis of AIS remains to be further researched. Level of Evidence: Level III (Diagnostic Study)